Empirical Research on Internal Audit Position of Companies in Serbia - Ljubisavljevic, Snežana; Jovanovic, Dejan (Economic Annals, 2011)
In the context of the globalization of business operations and the increasing use of information technologies, complexity of business transactions, and business risk, the role of internal audit is becoming increasingly important and the range of tasks performed by internal auditors is growing. As a part of the company control system, the internal audit assesses the efficiency, effectiveness, economy, and fairness of the realization of tasks, provides consulting services to the enterprise’s management, and promotes the effectiveness of risk management with the aim of creating added value and enhancing business activities. It is the aim of this work, through empirical research conducted in large and medium-sized Serbian companies, to show the degree of development of the internal audit, the perception of accountants in respect to the tasks and responsibilities of internal audit, and whether there is a connection between the enterprise size and legal form on the one hand, and the organization and responsibilities of internal audit on the other.